Preparation method of carbon fiber reinforced epoxy resin prepreg
By adding dicyclopentadiene and Grubbs second-generation catalyst to the carbon fiber/epoxy resin composite material, a crosslinking network structure is formed, which solves the problem of insufficient toughness of the composite material, achieves high toughness and good laying properties, and improves the overall performance of the composite material.
Patent Information
- Application Number
- CN202311431178.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The existing carbon fiber/epoxy resin composites have low toughness, prone to impact damage and stratification failure, which limits its further application.
By adding dicyclopentadiene (DCPD) curing system to the epoxy resin and using Grubbs second-generation catalyst, a mixed resin between the polybicyclopentadiene curing system and the epoxy resin curing system is formed. The gradual heating polymerization is used to achieve the first curing of dicyclopentadiene, forming a crosslinking network structure, and improving the toughness of the resin.
The high toughness of carbon fiber-reinforced epoxy resin prepreg is achieved, the interlayer fracture toughness of the composite material is improved, the surface has viscosity and good laying properties, and full curing is achieved at high temperature.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of resin materials, and in particular relates to a method for preparing a high-toughness carbon fiber reinforced epoxy resin prepreg. Background Art
[0002] Carbon fiber / epoxy resin (CF / EP) composite materials are an important branch of carbon fiber (CF) reinforced composite materials. In recent years, as people's understanding of EP / CF composite materials continues to deepen, due to its excellent comprehensive properties such as high specific strength, high specific modulus, strong designability, corrosion resistance, fatigue resistance, and easy overall molding, it has first been widely used in the fields of aviation and aerospace, prompting it to rapidly expand to other fields and its usage has continued to increase.
[0003] However, the inherent brittleness of epoxy resin leads to low toughness of composite materials based on it, which is easy to be damaged by impact and delaminate, limiting its further application. Therefore, how to increase the toughness of epoxy resin and thus improve the overall performance of liquid molding composite materials has very important theoretical significance and application value, and has become an important research topic in the field of composite materials.
[0004] By adding dicyclopentadiene (DCPD) curing system in epoxy matrix, it has been proved that the toughening of epoxy resin is feasible, but there are few related patent reports on polydicyclopentadiene (PDCPD) toughening epoxy resin composite materials. CN102286139A reports a toughening epoxy resin composition containing dicyclopentadiene alicyclic structure. However, due to the fact that only DCPD is added in the patent application, and no catalyst of DCPD is added, DCPD will not react with epoxy resin, nor will it react with anhydride, that is, cyclopentadiene cannot react with epoxy group and anhydride group in the absence of catalyst; therefore, after the epoxy resin is cured in the later stage, DCPD is still a small molecule in epoxy resin, so the toughening effect of the method needs to be further improved. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a method for preparing a high-toughness carbon fiber reinforced epoxy resin prepreg, comprising the following steps:
[0006] S1: Preparation of dicyclopentadiene resin system: dissolving Grubbs II catalyst and tributyl phosphite in cyclohexylbenzene to prepare a catalyst solution, and mixing the prepared catalyst solution with dicyclopentadiene;
[0007] S2: Epoxy resin system preparation: Mix the anhydride curing agent and accelerator with the epoxy resin;
[0008] S3: adding the dicyclopentadiene resin system prepared in S1 to the epoxy resin system prepared in S2, stirring the two thoroughly, mixing them evenly, and storing them at a constant temperature;
[0009] S4: lay the cut carbon fiber cloth on the release paper, pour the resin prepared in S3 on the surface, then place it between two stainless steel plates, put it into a press, increase the temperature and pressure, and take it out to obtain the prepreg.
[0010] Preferably, in step S1, the molar ratio of the Grubbs second-generation catalyst to dicyclopentadiene is 1:(5000-15000); the molar ratio of the Grubbs second-generation catalyst to tributyl phosphite is 1:(0.05-0.25); the mass ratio of the Grubbs second-generation catalyst to cyclohexylbenzene is 1:(100-400); the dissolution temperature of the catalyst in cyclohexylbenzene is 40-60°C, and the dissolution time is 30-60 minutes; the dicyclopentadiene monomer is a mixture of cyclopentadiene and norbornene, and the mass fraction of norbornene is 3%-5%.
[0011] Preferably, in step S2, the epoxy resin is a bisphenol A epoxy resin; the anhydride curing agent is selected from one or more of methyl nadic anhydride, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride, and phthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30); and the ratio of the components is epoxy resin: anhydride curing agent: accelerator = 100: (80-85): (3-5).
[0012] Preferably, in step S3, the dicyclopentadiene resin system accounts for 5% to 30% of the total mass of the mixed resin; and the constant temperature storage temperature is 15 to 30°C.
[0013] Preferably, in step S4, the carbon fiber is T300, T700 or T800, and the tow is 3K, 6K or 12K; the ratio of the amount of resin poured into the fiber surface to the fiber mass is 1:(1-2); in the heating step, the temperature is 60-90°C, the pressure is 0.25MPa-0.75MPa, and the insulation time is 30-60 minutes.
[0014] The beneficial effects of the present invention are:
[0015] (1) In the present invention, during the curing process of the mixed resin containing the polydicyclopentadiene curing system and the epoxy resin curing system, the cyclopentadiene first undergoes ring-opening metathesis polymerization to form a cross-linked network structure, and the epoxy resin small molecules are distributed in the gaps of the network structure. At this time, the resin is in an elastic state, and when the temperature is further increased, the epoxy resin will polymerize. This curing characteristic can be well applied to the preparation process of prepregs to prepare prepregs in which the polydicyclopentadiene is completely cured and the epoxy resin is not cured.
[0016] (2) The matrix resin used in the present invention is a mixed resin of an epoxy resin / anhydride curing system and a dicyclopentadiene / Grubbs second-generation catalyst system. The dicyclopentadiene can be cured first by gradually increasing the temperature for polymerization. The prepreg is in an elastic state, has a sticky surface, and has good paving properties. After being heated to a high temperature, the prepreg is fully cured. The composite material prepared using the prepreg provided by the present invention has excellent interlaminar fracture toughness. DETAILED DESCRIPTION
[0017] The present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only used to illustrate the invention, but do not limit the scope of the present invention in any form. In addition, it should be noted that those skilled in the art can make various modifications and improvements to the present invention. These all belong to the protection scope of the present invention.
[0018] Example 1
[0019] (1) Grubbs second-generation catalyst and cyclohexylbenzene are prepared in a mass ratio of 1:100, and the temperature is raised to 60°C. After 1 hour, the catalyst is completely dissolved, and then a retarder is added in a molar ratio of catalyst to tributyl phosphite of 1:0.05. The catalyst solution is placed at room temperature for use. The molar ratio of catalyst to DCPD monomer is 1:10000, and the amount of catalyst solution is calculated based on the catalyst concentration in (1), and added to the dicyclopentadiene monomer (norbornene content is 5%), and the dicyclopentadiene resin system is prepared.
[0020] (2) E51 epoxy resin, methyl nadic anhydride and DMP-30 were mixed and stirred in a mass ratio of 100:85:3. The epoxy resin system was prepared.
[0021] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 20:80, and mixed and stirred evenly.
[0022] (4) Cut a certain size of T300 3K plain weave cloth with a surface density of 200 gsm, place it on the surface of the release paper, pour the resin prepared in (3) into it, and the mass ratio of resin to carbon fiber is 1:2. Cover the surface with another layer of release paper, place it between two stainless steel plates, and put it into the press.
[0023] (5) The temperature was raised to 75°C and the pressure was raised to 0.25 MPa. After 1 hour, the steel plate was removed.
[0024] The above prepreg was cured by vacuum bag vacuuming process, and the curing system was 120℃ for 2 hours, 150℃ for 4 hours, and 180℃ for 2 hours. The panels were made and the performance after vacuum bag curing was tested: Type I interlaminar fracture toughness can reach 1034J / ㎡, and Type II fracture toughness can reach 1643J / ㎡
[0025] Example 2
[0026] (1) Grubbs second-generation catalyst and cyclohexylbenzene are prepared at a mass ratio of 1:200, and the temperature is raised to 45°C. After half an hour, the catalyst is completely dissolved, and then a retarder is added at a molar ratio of catalyst to tributyl phosphite of 1:0.1. The catalyst solution is placed at room temperature for use. The molar ratio of catalyst to DCPD monomer is 1:5000, and the amount of catalyst solution is calculated based on the catalyst concentration in (1), and added to the dicyclopentadiene monomer (norbornene content is 4%), and the dicyclopentadiene resin system is prepared.
[0027] (2) Mix E51 epoxy resin, methyltetrahydrophthalic anhydride and DMP-30 in a mass ratio of 100:80:5. The epoxy resin system is ready.
[0028] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 5:95, and mixed and stirred evenly.
[0029] (4) Cut a certain size of T700 6K plain weave cloth with a surface density of 200 gsm, place it on the surface of the release paper, pour the resin prepared in (3) into it, and the mass ratio of resin to carbon fiber is 1:1.5. Cover the surface with another layer of release paper, place it between two stainless steel plates, and put it into the press.
[0030] (5) Raise the temperature to 60°C and the pressure to 0.5 MPa, and remove the steel plate after half an hour.
[0031] The above prepreg was cured by vacuum bag vacuuming process, and the curing system was 120℃ for 2 hours, 150℃ for 4 hours, and 180℃ for 2 hours. The panels were made and the performance after vacuum bag curing was tested: Type I interlaminar fracture toughness can reach 933J / ㎡, and Type II fracture toughness can reach 1486J / ㎡
[0032] Example 3
[0033] (1) The Grubbs second-generation catalyst and cyclohexylbenzene are prepared at a mass ratio of 1:400, and the temperature is raised to 40° C. After 45 minutes, the catalyst is completely dissolved, and then a retarder is added at a molar ratio of catalyst to tributyl phosphite of 1:0.25, and the catalyst solution is placed at room temperature for use. The molar ratio of catalyst to DCPD monomer is 1:15000, and the amount of catalyst solution is calculated based on the catalyst concentration in (1), and added to the dicyclopentadiene monomer (norbornene content is 3%), and the dicyclopentadiene resin system is prepared.
[0034] (2) Mix E51 epoxy resin, phthalic anhydride and DMP-30 in a mass ratio of 100:82:3. The epoxy resin system is ready.
[0035] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 30:70, and mixed and stirred evenly.
[0036] (4) Cut a certain size of T800 12K plain weave cloth with a surface density of 200 gsm, place it on the surface of the release paper, pour the resin prepared in (3) into it, and the mass ratio of resin to carbon fiber is 1:1. Cover the surface with another layer of release paper, place it between two stainless steel plates, and put it into the press.
[0037] (5) The temperature was raised to 90°C and the pressure was raised to 0.75 MPa. After 45 minutes, the steel plate was removed.
[0038] The above prepreg was cured by vacuum bag vacuuming process, and the curing system was 120℃ for 2 hours, 150℃ for 4 hours, and 180℃ for 2 hours. The panels were made and the performance after vacuum bag curing was tested: Type I interlaminar fracture toughness can reach 1813J / ㎡, and Type II fracture toughness can reach 2367J / ㎡
[0039] Example 4
[0040] (1) Grubbs second-generation catalyst and cyclohexylbenzene are prepared at a mass ratio of 1:200, and the temperature is raised to 45°C. After half an hour, the catalyst is completely dissolved, and then a retarder is added according to a molar ratio of catalyst to tributyl phosphite of 1:0.1. The catalyst solution is placed at room temperature for use. The molar ratio of catalyst to DCPD monomer is 1:5000, and the amount of catalyst solution is calculated based on the catalyst concentration in (1), and added to the dicyclopentadiene monomer (norbornene content is 5%), and the dicyclopentadiene resin system is prepared.
[0041] (2) E51 epoxy resin, methyl hexahydrophthalic anhydride and DMP-30 were mixed and stirred in a mass ratio of 100:85:5. The epoxy resin system was configured.
[0042] (3) The dicyclopentadiene resin system prepared in (1) and the epoxy resin prepared in (2) are prepared in a mass ratio of 15:85, and mixed and stirred evenly.
[0043] (4) Cut a certain size of T300 3K plain weave cloth with a surface density of 200 gsm, place it on the surface of the release paper, pour the resin prepared in (3) into it, and the mass ratio of resin to carbon fiber is 1:1. Cover the surface with another layer of release paper, place it between two stainless steel plates, and put it into the press.
[0044] (5) Raise the temperature to 60°C and the pressure to 0.5 MPa, and remove the steel plate after half an hour.
[0045] The above prepreg was cured by vacuum bag vacuuming process, and the curing system was 120℃ for 2 hours, 150℃ for 4 hours, and 180℃ for 2 hours. The panels were made and the performance after vacuum bag curing was tested: Type I interlaminar fracture toughness can reach 865J / ㎡, and Type II fracture toughness can reach 1252J / ㎡
[0046] Comparative Example 1
[0047] When there is no cyclopentadiene system in the epoxy system, the prepreg cannot be prepared using the molding process described in this patent, so in the comparative example, vacuum-assisted infusion molding is directly used to prepare the epoxy resin / anhydride / carbon fiber composite material.
[0048] According to the VARI process, lay a certain size of T300 3K plain cloth with a surface density of 200gsm, demoulding cloth, guide net, and vacuum bag to seal the entire system. Then, the gas inside the mold cavity is extracted under vacuum negative pressure, and E51 epoxy resin, methyl hexahydrophthalic anhydride and DMP-30 are mixed and stirred at a mass ratio of 100:85:5, and poured into the carbon fiber at 60℃. The curing system is 120℃ for 2 hours, 150℃ for 4 hours, and 180℃ for 2 hours. The board is made and the performance after vacuum bag curing is tested: Type I interlaminar fracture toughness can reach 365J / ㎡, and Type II fracture toughness can reach 813J / ㎡
[0049] Comparative Example 2
[0050] According to the VARI process, lay a certain size of T300 3K plain cloth with a surface density of 200gsm, demoulding cloth, guide net, and vacuum bag to seal the entire system. Then, the gas inside the mold cavity is extracted under vacuum negative pressure, and E51 epoxy resin, methyl nadic anhydride and DMP-30 are mixed and stirred at a mass ratio of 100:85:5, and poured into the carbon fiber at 60℃. The curing system is 120℃ for 2 hours, 150℃ for 4 hours, and 180℃ for 2 hours. The board is made and the performance after vacuum bag curing is tested: Type I interlaminar fracture toughness can reach 327J / ㎡, and Type II fracture toughness is 779J / ㎡
[0051] Table 1 Fracture toughness test results of embodiments and comparative examples
[0052] Interlaminar Mode I fracture toughness Interlaminar Mode II Fracture Toughness Example 1 1034 1643 Example 4 865 1252 Comparative Example 1 365 813 Comparative Example 2 327 779
[0053] As shown in Table 1, the carbon fiber reinforced epoxy resin prepreg obtained by the method proposed in the present invention has a fracture toughness that is greatly improved compared with the prepreg obtained by the conventional method of the prior art. This fully demonstrates that the matrix resin is a mixed resin of an epoxy resin / anhydride curing system and a dicyclopentadiene / Grubbs second-generation catalyst system, and the dicyclopentadiene can be cured first by gradually increasing the temperature for polymerization. The prepreg is in an elastic state, has a sticky surface, and has good paving properties. After being raised to a high temperature, the prepreg is fully cured, and the composite material prepared by the prepreg provided by the present invention has excellent interlaminar fracture toughness.
[0054] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not limit it. Although this patent is described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions recorded in the aforementioned embodiments or to replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber reinforced epoxy resin prepreg, characterized in that: The following steps are involved: S1: Preparation of dicyclopentadiene resin system: dissolving Grubbs II catalyst and tributyl phosphite in cyclohexylbenzene to prepare a catalyst solution, and mixing the prepared catalyst solution with dicyclopentadiene; S2: Epoxy resin system preparation: Mix the anhydride curing agent and accelerator with the epoxy resin; S3: adding the dicyclopentadiene resin system prepared in S1 to the epoxy resin system prepared in S2, stirring the two thoroughly, mixing them evenly, and storing them at a constant temperature; S4: lay the cut carbon fiber cloth on the release paper, pour the resin prepared in S3 on the surface, then place it between two stainless steel plates, put it into a press, increase the temperature and pressure, and take it out to obtain the prepreg.
2. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The molar ratio of the Grubbs second generation catalyst to dicyclopentadiene in step S1 is 1:(5000-15000).
3. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: In step S1, the molar ratio of the Grubbs second generation catalyst to tributyl phosphite is 1:(0.05-0.25).
4. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The mass ratio of the Grubbs second generation catalyst to cyclohexylbenzene in step S1 is 1:(100-400).
5. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: In step S1, the catalyst is dissolved in cyclohexylbenzene at a temperature of 40 to 60° C. for 30 to 60 minutes.
6. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The dicyclopentadiene monomer in step S1 is a mixture of cyclopentadiene and norbornene, and the mass fraction of norbornene is 3% to 5%.
7. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The epoxy resin in step S2 is bisphenol A epoxy resin.
8. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The anhydride curing agent in step S2 is selected from one or more of methyl nadic anhydride, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride and phthalic anhydride.
9. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The accelerator in step S2 is 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30).
10. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The ratio of the components in step S2 is epoxy resin: anhydride curing agent: accelerator = 100: (80-85): (3-5).
11. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The dicyclopentadiene resin system in step S3 accounts for 5% to 30% of the total mass of the mixed resin.
12. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: The constant temperature storage temperature in step S3 is 15-30°C.
13. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: In step S4, the carbon fiber is T300, T700 or T800, and the tow is 3K, 6K or 12K.
14. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: In step S4, the ratio of the amount of resin poured onto the fiber surface to the fiber mass is 1:(1-2).
15. The method for preparing a carbon fiber reinforced epoxy resin prepreg according to claim 1, characterized in that: In the heating step in step S4, the temperature is 60 to 90° C., the pressure is 0.25 MPa to 0.75 MPa, and the insulation time is 30 to 60 minutes.
Citation Information
Patent Citations
A toughened epoxy resin composition containing a dicyclopentadiene alicyclic structure
CN102286139A